THE EFFECTIVENESS OF AI-BASED DIGITAL LEARNING ENVIRONMENTS IN FOREIGN LANGUAGE TEACHING (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article analyzes the didactic potential of artificial intelligence (AI) technologies in foreign language teaching, with a particular focus on English language instruction. It explores how AI-powered interactive platforms, automated assessment systems, personalized learning trajectories, and communication-based intelligent agents can enhance the effectiveness of language education. The study emphasizes the role of AI in the educational process and its pedagogical integration into foreign language teaching.